2017
DOI: 10.1055/s-0037-1604395
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome and Secondary Operations after Proximal Row Carpectomy or Four-Corner Arthrodesis

Abstract: Proximal row carpectomy (PRC) and four-corner arthrodesis (FCA) are common surgical procedures used to treat degenerative wrist conditions; however, complications and failures can occur. This study aimed to investigate and compare the long-term rate of secondary surgeries including conversion to total wrist arthrodesis in patients who underwent PRC or FCA. A retrospective chart review of all patients who underwent PRC or FCA in the past 20 years at a tertiary referral institution and associated Veterans Affair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
5
21
1
Order By: Relevance
“…They saw no significant differences in conversion rate to total wrist arthrodesis in the PRC group versus 4 CF group patients [37]. In overall conclusion of a randomized clinical trial comparing proximal row carpectomy and four-corner fusion, Aita et al resumed no significant statistical differences in clinical and functional results between both salvage procedures [38].…”
Section: Discussionmentioning
confidence: 99%
“…They saw no significant differences in conversion rate to total wrist arthrodesis in the PRC group versus 4 CF group patients [37]. In overall conclusion of a randomized clinical trial comparing proximal row carpectomy and four-corner fusion, Aita et al resumed no significant statistical differences in clinical and functional results between both salvage procedures [38].…”
Section: Discussionmentioning
confidence: 99%
“…Articles that included appropriate data were reviewed for bibliographic citations related to the above keywords in a secondary search for complication and return-to-work rates. Data from 11 reports were used to define complication rates for PRC 3 , 9 , 18 , 22 , 23 , 29 , 34 , 36 - 39 , and 17 were used for FCA complication rates 3 , 9 , 18 , 19 , 22 , 27 , 29 , 34 , 36 - 38 , 40 - 45 (Table I). One of these sources was a published abstract that contained data on the timing of complications following the index surgical procedures 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Clinical outcomes, or health states or utilities, are integral in determining the cost-effectiveness of a given treatment. Numerous studies have assessed the clinical outcomes of PRC and FCA 3 , 6 - 22 . Two systematic reviews of PRC and FCA outcomes did not identify any differences in patient-reported disability, subjective ratings of satisfaction, rate of conversion to total wrist arthrodesis, or increase in grip strength 7 , 8 .…”
mentioning
confidence: 99%
“…64 However, several other studies have reported a significantly larger number of patients with secondary arthritic changes after PRC, although most are symptom free. 65 There is a lack of well-conducted studies, but Mulford et al 60 reported and confirmed in a systematic review that both 4CF and PRC produce a clear improvement in pain and subjective outcome measurements for patients with symptomatic SLAC wrists. PRC can perhaps provide a better postoperative ROM, with less risk of the potential complications specific to 4CF (10% more complications occurring; such as nonunion, hardware problems, and dorsal impingement).…”
Section: Bone Marrow Stimulationsmentioning
confidence: 99%